2016
DOI: 10.1093/brain/aww280
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative automated fibre quantification predicts postoperative seizure outcome in temporal lobe epilepsy

Abstract: Around half of all patients fail to achieve seizure freedom after temporal lobe resection. Keller et al. show that postoperative seizures after amygdalohippocampectomy are associated with regional tissue abnormalities and insufficient resection of temporal lobe white matter tracts. These results hold promise as imaging prognostic markers of postoperative seizure outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 90 publications
5
97
0
Order By: Relevance
“…Consequently, tractography may provide insight into different patterns of brain damage related to the laterality, type of epilepsy or epileptogenic lesion while along-the-tract analysis of diffusion metrics may also allow extraction of detailed information regarding neuropathology in epilepsy. It may have the potential to identify certain abnormal brain regions in individual patients (Martin et al, 2015), allow inferences about seizure onset zones or may even predict surgical outcomes (Keller et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, tractography may provide insight into different patterns of brain damage related to the laterality, type of epilepsy or epileptogenic lesion while along-the-tract analysis of diffusion metrics may also allow extraction of detailed information regarding neuropathology in epilepsy. It may have the potential to identify certain abnormal brain regions in individual patients (Martin et al, 2015), allow inferences about seizure onset zones or may even predict surgical outcomes (Keller et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Each patient underwent a detailed presurgical program, including comprehensive seizure semiology assessment, MRI, neuropsychological assessment, interictal electroencephalography and if clinically necessary, additional invasive electrophysiological recordings, as reported recently 10, 32. All patients showed evidence of a unilateral temporal lobe seizure onset with concomitant ipsilateral HS.…”
Section: Methodsmentioning
confidence: 99%
“…HS was identified by an expert neuroradiologist with considerable experience in lesion diagnosis in epilepsy, which was defined by hippocampal volume loss and internal structure disruption on T1w images, and/or hyperintensities on T2w and FLAIR images 10. There was no evidence of bilateral HS in any patient; all patients had seizures of presumed unilateral temporal lobe origin, and there was no evidence of a secondary extrahippocampal lesion that may have contributed to seizures 32. All patients underwent standardized amygdalohippocampectomy and routine diagnostic analysis of resected hippocampal specimens by an experienced neuropathologist 10.…”
Section: Methodsmentioning
confidence: 99%
“…However, we suggest that there remains the possibility that common structural network alterations may exist in patients with NDfE, and which may be beyond the resolution of VBM. Advanced diffusionbased MRI approaches Glenn et al, 2016;Keller et al, 2017) may provide important insights into structural network alterations in NDfE. Furthermore, a recently published study has shown that pathological structural connectivity causes disturbances to common large-scale functional brain networks regardless of the localization of the epileptogenic zone in patients with refractory focal epilepsy (Besson et al, 2017).…”
Section: Biological and Clinical Implicationsmentioning
confidence: 99%
“…Sophisticated MRI approaches in particular have provided a deeper understanding of the biological mechanisms underlying the development of focal and generalized epilepsies (Bernhardt, Hong, Bernasconi, & Bernasconi, 2013;Duncan, 2005;Koepp & Woermann, 2005), and have recently been used to gain insights into response to surgical intervention in patients with refractory focal epilepsy Keller et al, 2015Keller et al, , 2017Munsell et al, 2015). Sophisticated MRI approaches in particular have provided a deeper understanding of the biological mechanisms underlying the development of focal and generalized epilepsies (Bernhardt, Hong, Bernasconi, & Bernasconi, 2013;Duncan, 2005;Koepp & Woermann, 2005), and have recently been used to gain insights into response to surgical intervention in patients with refractory focal epilepsy Keller et al, 2015Keller et al, , 2017Munsell et al, 2015).…”
Section: Introductionmentioning
confidence: 99%